BuqiTongluo Granule for Ischemic Stroke, Stable Angina Pectoris, Diabetic Peripheral Neuropathy with Qi Deficiency and Blood Stasis Syndrome: Rationale and Novel Basket Design - Liu, Weidi; Zhou, Li; Feng, Luda; Zhang, Dandan; Zhang, Chi; Gao, Ying, behalf of the BOSS Group (Frontiers in Pharmacology, 2021)
Background: BuqiTongluo (BQTL) granules are herbal phenotypic drugs for Qi deficiency and blood stasis (QDBS) syndrome. Its discovery relied primarily on knowledge of observable phenotypic changes associated with diseases. Although BQTL granules have been widely advocated by Chinese Medicine (CM) practitioners, its use lacks empirical support. Aim of the study: In this basket trial, the efficacy of BQTL granules in multiple diseases that have the QDBS syndrome in common will be compared with placebo. Materials and Methods: The BuqiTongluo granule for Qi deficiency and blood stasis syndrome (BOSS) study is a basket herbal trial (ClinicalTrials.gov, NCT04408261). It will be a double-blinded, randomized, placebo-controlled, parallel, multicenter, clinical trial. In total, 432 patients (1:1:1 ischemic stroke, stable angina pectoris, and diabetic peripheral neuropathy), who meet the operationalized diagnostic criteria for QDBS syndrome, have been recruited and randomized in a ratio of 1:1 to receive 6 weeks’ treatment with BQTL granules or placebo. The primary outcome is the change in the QDBS syndrome score at week 6 from baseline. Secondary outcomes include objective outcome measures for the three diseases and adverse events. Omics will help to understand these responses by molecular events. Conclusion: QDBS syndrome is a common phenotypic marker that was hypothesized to predict whether patients with multiple diseases would respond to this targeted therapy. No previous basket trial has assessed the potential efficacy of an herbal intervention for multiple diseases. The unique promise of the trial is its ability to exploit a disease phenotype to discover novel treatments for three diseases for which the root cause is unknown, complex, or multifactorial, and for which scientific understanding is insufficient to provide valid molecular targets.